2004
DOI: 10.1128/aem.70.4.2529-2534.2004
|View full text |Cite
|
Sign up to set email alerts
|

ω-Amino Acid:Pyruvate Transaminase from Alcaligenes denitrificans Y2k-2: a New Catalyst for Kinetic Resolution of β-Amino Acids and Amines

Abstract: Alcaligenes denitrificans Y2k-2 was obtained by selective enrichment followed by screening from soil samples, which showed -amino acid:pyruvate transaminase activity, to kinetically resolve aliphatic ␤-amino acid, and the corresponding structural gene (aptA) was cloned. The gene was functionally expressed in Escherichia coli BL21 by using an isopropyl-␤-D-thiogalactopyranoside (IPTG)-inducible pET expression system (9.6 U/mg), and the recombinant AptA was purified to show a specific activity of 77.2 U/mg for L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 25 publications
2
60
0
Order By: Relevance
“…In the case of the amino acceptor, 2-ketoglutarate, pyruvate ethyl ester, pyruvate, and pyruvate methyl ester showed similar reactivities, while oxaloacetate showed slightly lower reactivity. It is quite interesting that this enzyme has no striking differences in the specificities toward different amino acceptors, because transaminases generally show a clear preference either for pyruvate or for 2-ketoglutarate/oxaloacetate (33,47,48,52,56). However, considering the fact that this enzyme shows a high sequence similarity with the GSA which does not need any second substrate and catalyzes the intramolecular isomerization, it is possible that the unique amino acceptor specificity could be due to different structural reasons with other transaminases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the amino acceptor, 2-ketoglutarate, pyruvate ethyl ester, pyruvate, and pyruvate methyl ester showed similar reactivities, while oxaloacetate showed slightly lower reactivity. It is quite interesting that this enzyme has no striking differences in the specificities toward different amino acceptors, because transaminases generally show a clear preference either for pyruvate or for 2-ketoglutarate/oxaloacetate (33,47,48,52,56). However, considering the fact that this enzyme shows a high sequence similarity with the GSA which does not need any second substrate and catalyzes the intramolecular isomerization, it is possible that the unique amino acceptor specificity could be due to different structural reasons with other transaminases.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, transaminases allow asymmetric synthesis from prochiral ketone compounds depending upon the properties of target chemical compounds (1,4,10,11,17,49,50). Though transaminases are not widespread, we have reported an -transaminase of Alcaligenes denitrificans which can catalyze mainly the transamination between aliphatic ␤-amino acids and pyruvate (56). Other examples were recently introduced for the transamination of aliphatic and aromatic ␤-amino acids by Alcaligenes eutrophus and Variovorax paradoxus (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the microbial metabolism of -amino acids, such as -alanine, -aminoisobutyrate, -aminobutyrate and taurine, metabolism through transamination catalyzed by !-amino acid transaminases has been reported. [12][13][14] Until now, there has been no report on BPA metabolism. In this study, it was found that one type of BPA metabolism involves transamination that is the same as some other -amino acid metabolisms.…”
Section: Discussionmentioning
confidence: 99%
“…35) Mll3663 gene product, predicted as an amine:pyruvate AT, showed high activity towards secondary aromatic amines like (S)--methylbenzylamine (A1) and 1-phenylpropylamine (A2), but no or very low activity towards -amino acids (C1, C2, and D1). This enzyme showed rather narrow substrate specificity.…”
Section: Experimental Investigation Of the Functions Of The Putativementioning
confidence: 99%